Marine Isotope Stage 4 glaciation in northern England, UK: Evidence from Victoria Cave, North Yorkshire - Tom C. Lord; Peter Wilson; Joyce Lundberg; Adrian P. Palmer; Matt W. Telfer; Rhiannon E. Stevens; Phillip J. Murphy; Mark Lewis (Journal of Quaternary Science, 2026)
Victoria Cave, north Yorkshire, England, contains a long sequence of Pleistocene clastic sediments and calcite flowstones. Earlier work, using U–Th dating, established that the flowstone units formed in interglacial stages corresponding to Marine Isotope Stages (MIS) 13, 11, 9, 7 and 5. The intervening laminated sediments were therefore assigned to glacial stages (MIS 12, 10, 6 and 2) and regarded as rhythmites that settled from ponded glacial meltwater in the cave. Victoria Cave is a rare instance of cave rhythmites that formed over a number of glacial–interglacial cycles. The macro‐ and micromorphologies of the rhythmites support the above interpretation, and the mineralogy demonstrates that the sediments probably derive from rock types within the local area. An OSL age of 66 ± 8.4 ka from the uppermost unit of the rhythmites and two 14 C ages of 46.1–54.9 cal. ka BP and 48.9–>55.0 cal. ka BP, for horse and reindeer, respectively, from the overlying Bone‐bearing Cave Earth provide a new chronology for these Late Pleistocene sediments. Together, these results indicate that the youngest rhythmites in Victoria Cave formed during MIS 4 and not MIS 2 as previously assumed. This provides strong support for more widespread glaciation in northern England in MIS 4 (~71–59 ka) than has previously been recognised. The MIS 4 rhythmites represent the most tightly constrained cave rhythmites in Britain and the first terrestrial‐based evidence from this area for glaciation at that time.